Three types of rescue can avert extinction in a changing environment - Hufbauer, Ruth A; Szűcs, Marianna; Kasyon, Emily; Youngberg, Courtney; Koontz, Michael J; Richards, Christopher; Tuff, Ty; Melbourne, Brett A (Proceedings of the National Academy of Sciences - PNAS, 2015)
Setting aside high-quality large areas of habitat to protect threatened populations is becoming increasingly difficult as humans fragment and degrade the environment. Biologists and managers therefore must determine the best way to shepherd small populations through the dual challenges of reductions in both the number of individuals and genetic variability. By bringing in additional individuals, threatened populations can be increased in size (demographic rescue) or provided with variation to facilitate adaptation and reduce inbreeding (genetic rescue). The relative strengths of demographic and genetic rescue for reducing extinction and increasing growth of threatened populations are untested, and which type of rescue is effective may vary with population size. Using the flour beetle (Tribolium castaneum) in a microcosm experiment, we disentangled the genetic and demographic components of rescue, and compared them with adaptation from standing genetic variation (evolutionary rescue in the strictest sense) using 244 experimental populations founded at either a smaller (50 individuals) or larger (150 individuals) size. Both types of rescue reduced extinction, and those effects were additive. Over the course of six generations, genetic rescue increased population sizes and intrinsic fitness substantially. Both large and small populations showed evidence of being able to adapt from standing genetic variation. Our results support the practice of genetic rescue in facilitating adaptation and reducing inbreeding depression, and suggest that demographic rescue alone may suffice in larger populations even if only moderately inbred individuals are available for addition.